Effect on cost of capital of Syngenta Bangladesh Limited by lntroducing public share: a comparative analysis with Square Pharmaceuticals Limited and ACI Limited - Biswas, Bless Showmick (2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.